Preparation method and application of temperature-sensitive hydrogel doped with silver ion Ag (at) Pr < 3 + >: Y2SiO5 up-conversion material

By combining the doped silver ion Ag@Pr3+:Y2SiO5 upconversion material with chitosan, dopamine, pyrrole and β-glycerol sodium phosphate, a multifunctional temperature-sensitive hydrogel was prepared, which solved the problem of limited application effects of existing upconversion materials and poor structural uniformity of metal phosphate crosslinked hydrogels, and achieved reversible transformation and multiple functions of the hydrogel, improving the intelligence and therapeutic effect of biomedical materials.

CN119633162APending Publication Date: 2025-03-18CHANGZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608170.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The application effect of existing upconversion materials in UV therapy is limited, and the structural uniformity and repeatability of metal phosphate-crosslinked chitosan hydrogels are poor, and no reports of their reversible transformation have been seen.

Method used

The silver-doped Ag@Pr3+:Y2SiO5 upconversion material was combined with chitosan, dopamine, pyrrole and β-glycerol phosphate to prepare a multifunctional temperature-sensitive hydrogel with good biocompatibility, antibacteriality, drug release regulation and photoresponse characteristics.

Benefits of technology

The sol-gel reversible transformation of hydrogels has been achieved, which improves the intelligence and adaptability of biomedical materials, effectively kills pathogens, reduces drug resistance problems, and improves the therapeutic effect through photocontrol drug release regulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130203270000031
    Figure BDA0005130203270000031
  • Figure BDA0005130203270000071
    Figure BDA0005130203270000071
  • Figure BDA0005130203270000081
    Figure BDA0005130203270000081
Patent Text Reader

Abstract

The invention belongs to the technical field of optical materials, and particularly relates to a preparation method and application of a temperature-sensitive hydrogel doped with a silver ion Ag (at) Pr < 3 + >: Y2SiO5 up-conversion material, Pr < 3 + >: Y2SiO5 nanoparticles are prepared firstly, surface amino modification is performed, modified yttrium praseodymium silicate, silver nitrate, KH-550 and trisodium citrate are mixed and reacted, and the Ag (at) Pr < 3 + >: Y2SiO5 up-conversion material is prepared. GP-HTCC-HEC temperature-sensitive hydrogel is prepared from chitosan, glycidyl trimethyl ammonium chloride, beta-glycerophosphate and hydroxyethyl cellulose, pyrrole and dopamine hydrochloride react to prepare PPY (at) PDA powder, and finally, the Ag (at) Pr < 3 + >: Y2SiO5 up-conversion material, the GP-HTCC-HEC and the PPY (at) PDA are mixed to obtain the temperature-sensitive hydrogel, so that reversible conversion of sol-gel can be realized, and light-operated drug release and antibacterial functions are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optical materials, and specifically relates to a silver ion-doped Ag@Pr 3+ :Preparation method and application of thermosensitive hydrogel of Y2SiO5 upconversion material. Background Art

[0002] So far, host materials, including fluoride, chloride and bromide, have been shown to enhance the upconversion luminescence intensity. As a substrate for upconversion materials, yttrium silicate Y2SiO5 has the characteristics of high thermal stability, good optical properties, simple manufacturing process, etc., and has been widely used in fluorescence technology, optical information storage and anti-counterfeiting technology. Surface plasmon resonance (SPR) caused by the collective oscillation of electrons on noble metal nanoparticles (NPs) is considered to be a new method to enhance luminescence emission. In general, the emission can be enhanced by adjusting the SPR absorption band to the excitation and / or emission band of the emitter. The SPR absorption band of noble metal nanoparticles is concentrated in the visible light region (Au: about 500-550nm, Ag: about 400-450nm). For organic and other fluorescent molecules, the absorption peak in the visible region is usually broad because each electronic state of the molecule is a different vibrational and rotational energy state. The luminescence enhancement of organic fluorescent molecules can be achieved using surface plasmon resonance technology.

[0003] In recent years, noble metal nanostructures have been frequently introduced to improve the upconversion luminescence efficiency of rare earth-doped nanomaterials. However, most of the obtained SPR absorption bands are too narrow, making it difficult for SPR to achieve a perfect overlap between the absorption band and the excitation / emission band of the luminescent RE ion, because the excitation / emission band in the visible region caused by the 4f intrashell transition is very narrow. More advanced rare earth-noble metal hybrid nanostructures need to be constructed to optimize the SPR-induced enhancement effect. The application of upconversion materials in ultraviolet light therapy has the potential to enhance its effect. Upconversion materials are a class of materials that can convert low-energy, long-wavelength light (such as infrared light) into high-energy, short-wavelength light (such as ultraviolet light). (It is recommended to analyze the problems or shortcomings of existing upconversion materials that convert infrared light into ultraviolet light. It is best to cite the analysis and highlight the actual technical problems to be solved.

[0004] Although chitosan (CS) has biodegradability, biocompatibility and antibacterial properties, it has been widely used to prepare thermosensitive hydrogels. However, when the molecular weight of CS is high, its solubility is poor, which is not conducive to the formation of hydrogel network structure. In order to improve its performance, researchers have introduced organic or inorganic crosslinkers to give chitosan new gel properties and constructed a chitosan-based smart hydrogel system. Among them, the hydrogel crosslinked with CS and transition metal ions exhibits advantages such as rapid gelation and simple operation, and has shown application potential in many fields.

[0005] Studies have shown that the use of metal ions (such as Ag + , Cu 2+ Chitosan hydrogels cross-linked with metal phosphates (such as Cu, etc.) can respond to changes in the external environment and have plasticity and the ability to maintain their shape for a long time. However, although these hydrogels have the potential for reversible gel-sol transformation, additional chemicals are usually required to promote this process. In addition, although some metal phosphate-crosslinked chitosan hydrogels have application potential in fields such as tissue engineering and catalyst recovery, due to the low solubility of metal phosphates, the structural uniformity and reproducibility of such hydrogels are poor, and there are no reports of their reversible transformation. A new type of hydrogel composed of metal cations (such as Cu 2+ 、Zn 2+ 、Cd 2+ 、Ni 2+ The high-water-content reversible thermosensitive hydrogel prepared by combining Ag and Cu with chitosan showed the ability to reversibly switch between the gel-sol state, especially the CS-Cu hydrogel showed good multiple switching characteristics. The development of antibacterial reversible thermosensitive hydrogel based on chitosan is of great significance in biomedicine, especially the use of Ag + Cross-linked antibacterial hydrogels, although there are few related studies, + It can bind to the DNA and thiol groups of microorganisms to form a stable complex, killing pathogens while effectively avoiding drug resistance. + Cross-linked reversible thermosensitive antibacterial hydrogels have broad application prospects. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a silver ion-doped Ag@Pr 3+ :A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material. The invention comprises a gel material prepared from dopamine, pyrrole, chitosan, sodium β-glycerophosphate, hydroxyethyl cellulose and the like and Ag@Pr 3+ : Y2SiO5 upconversion material is combined to design a multifunctional hydrogel material with good biocompatibility, antibacterial properties, drug release regulation and light response characteristics.

[0007] In order to achieve the above object, the technical solution provided by the present invention is:

[0008] A silver ion-doped Ag@Pr 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material comprises the following steps:

[0009] (1) Pr 3+:The preparation method of Y2SiO5 nanoparticles is as follows: take yttrium oxide (Y2O3) and add it to a dilute nitric acid HNO3 solution, then add nitric acid spectrum Pr(NO3)3 solution, heat to dissolve, heat with an electric furnace after dissolution, remove water, until the solution becomes viscous, stop heating, and a large number of crystals appear after cooling, and dry. Add the dried material into an ethanol solution to dissolve it, dissolve and add tetraethyl orthosilicate (TEOS) solution, stir and mix, put it into a 70°C water bath to form a gel, put the gel into 104°C to dry, and crush the sample with a mortar. Raise the temperature to 900°C by programmed heating, the heating rate is 8°C / min, and keep warm for 3 hours after reaching the set temperature to obtain Pr 3+ : Y2SiO5 nanoparticles.

[0010] The theoretical doping molar amount of Pr in Y2SiO5 relative to yttrium is 5%; the molar ratio of tetraethyl orthosilicate to yttrium oxide is 1:1.

[0011] (2) Pr 3+ Y2SiO5 nanoparticles were dispersed in water containing acetic acid, and then KH-550 was added. After stirring for 4 h, the amino-modified Pr 3+ : Y2SiO5 nanoparticles; washed twice with deionized water, and finally dispersed in deionized water to obtain yttrium praseodymium silicate (Pr 3+ :Y2SiO5) suspension.

[0012] (3) the yttrium praseodymium silicate (Pr 3+ The suspension of Y2SiO5 was heated to 90-110°C in an oil bath, and then aqueous solutions containing silver nitrate (AgNO3) and KH-550 were added in sequence. After stirring, trisodium citrate solution was added dropwise, and stirred for a period of time. The precipitate was collected, washed with deionized water for 6 times, and dried in a vacuum at 70°C for 24 hours. The obtained product was redispersed in anhydrous ethanol to obtain Ag@Pr 3+ : Y2SiO5 upconversion material dispersion, for use.

[0013] Among them, yttrium praseodymium silicate (Pr 3+ The molar ratio of :Y2SiO5), silver nitrate (AgNO3), and trisodium citrate is 0.02: 0.0009-0.0036: 0.0001-0.0026. The mass ratio of silver nitrate to KH-550 is 3:5-6.

[0014] (4) Quaternary ammonium chitosan was synthesized using chitosan and glycidyl trimethylammonium chloride (GTMAC) as raw materials and named N-[(2-hydroxy-3-trimethylammonium)propyl]chitosan chloride (HTCC):

[0015] HTCC was dissolved in a weak acid aqueous solution to obtain an HTCC solution. β-Glycerol phosphate (β-GP) was added to deionized water and mixed with the HTCC solution in an ice bath, and finally hydroxyethyl cellulose (HEC) was added to obtain a GP-HTCC-HEC thermosensitive hydrogel.

[0016] Further, a preparation method for synthesizing quaternized chitosan using chitosan and glycidyl trimethyl ammonium chloride (GTMAC) as raw materials is as follows: chitosan is dispersed in water, glycidyl trimethyl ammonium chloride (GTMAC) is added, and the mixture is kept in contact for 24 hours under stirring at 60°C. The reaction product is precipitated in acetone, and then filtered and dried in an oven at 60°C. The mass dosage relationship of chitosan and glycidyl trimethyl ammonium chloride is 1:2-1:2.5.

[0017]

[0018] Furthermore, the weak acid is acetic acid or lactic acid, and the concentration is 0.1 M; wherein the dosage relationship of HTCC, β-glycerophosphate, and hydroxyethyl cellulose is 0.1-0.5:2:1.

[0019] (5) PPY@PDA: Dissolve pyrrole monomer (PPy) and dopamine hydrochloride (HCl-PDA) in a Tris solution (pH=8.5, 0.01M) to obtain a (PPy-HCl-PDA-Tris) solution. After cooling in an ice-water bath, add the (PPy-HCl-PDA-Tris) solution dropwise to an aqueous solution of ammonium persulfate ((NH4)2S2O8), stir vigorously at low temperature, and then transfer to a refrigerator at 8°C and stir vigorously for 18 hours. After the reaction is completed, wash the precipitate with deionized water several times and collect it by centrifugation. Finally, freeze-dry the washed precipitate to obtain PPY@PDA powder. The molar ratio of pyrrole to dopamine hydrochloride is 6 to 8:1.

[0020] (6) Silver ion doping Ag@Pr 3+ :Preparation of thermosensitive hydrogel of Y2SiO5 upconversion material: Prepared Ag@Pr 3 + :Y2SiO5 upconversion material dispersion, GP-HTCC-HEC thermosensitive hydrogel, PPY@PDA, mixed and stirred to obtain silver ion-doped Ag@Pr 3+ : Thermosensitive hydrogel of Y2SiO5 upconversion material. The mass relationship of silver nitrate:β-glycerophosphate and dopamine hydrochloride in the raw materials is: 0.2-0.5:1:0.1-0.3.

[0021] More preferably, the molar ratio of AgNO3 to trisodium citrate is 0.0018:0.0004, which has the best up-conversion emission intensity at 310 nm, up to 200,000 cps.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The hydrogel prepared by the present invention realizes a reversible sol-gel transformation through temperature change, so that it can play different functions under different environmental conditions. This temperature sensitivity makes it particularly suitable for drug release and cell loading, improving the intelligence and adaptability of biomedical materials.

[0024] (2) Traditional antibacterial materials may cause pathogens to develop drug resistance, while the Ag prepared by the present invention + Cross-linked antibacterial hydrogels form stable complexes by combining with microbial DNA and thiol groups, which can effectively kill pathogens, reduce drug resistance problems, and show good results in antibacterial treatment.

[0025] (3) The present invention combines dopamine, pyrrole, chitosan, sodium β-glycerophosphate and upconversion materials to design a multifunctional hydrogel or composite material with good biocompatibility, antibacterial properties, drug release regulation and light response characteristics. Dopamine can self-polymerize under alkaline conditions to form polydopamine (PDA) with adhesive properties, which improves the adhesion of the hydrogel to the tissue surface and can be bonded to metal ions (Ag + ) to enhance the antibacterial properties. Pyrrole forms conductive polypyrrole (PPy) through polymerization, which gives the hydrogel conductivity and photothermal response properties, making it suitable for electrical stimulation tissue engineering or photothermal therapy. The combination of chitosan and sodium β-glycerophosphate forms a thermosensitive hydrogel, which has the characteristics of being in a solution state at low temperatures and a gel state at high temperatures. It can achieve minimally invasive injection and in situ coagulation, and is used for temperature-controlled release of drugs or growth factors.

[0026] (4) The upconversion material added in the present invention can convert low-energy infrared light into high-energy ultraviolet or visible light, realize light-controlled drug release and antibacterial function, and further regulate the drug release rate and area through the synergistic effect with the photothermal effect of polypyrrole, thereby reducing side effects. The composite material formed by this combination can be widely used in the fields of smart wound dressings, drug delivery, neural or cardiac tissue engineering, etc., and has multiple functions of antibacterial, conductive, temperature-sensitive and light-responsive, showing great application potential in the field of biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Ag@Pr 3+ :Schematic diagram of the preparation principle of thermosensitive hydrogel for Y2SiO5 upconversion material.

[0028] Figure 2 For Ag@Pr 3+ : XRD pattern of Y2SiO5.

[0029] Figure 3 Pr 3+ :Y2SiO5 and Ag@Pr 3+ : Up-conversion emission spectrum of Y2SiO5.

[0030] Figure 4 These are the adhesion and thermosensitivity characterization diagrams of the thermosensitive hydrogel and the modulus characterization diagrams.

[0031] Figure 5 SEM characterization of thermosensitive hydrogel.

[0032] Figure 6 (GP-HTCC-HEC-Pr 3+ : Potential diagram of Y2SiO5 upconversion material) and (GP-HTCC-HEC-Ag@Pr 3+ : Potential diagram of Y2SiO5 upconversion material).

[0033] Figure 7 For Ag@Pr 3+ :Chart of cytotoxicity test of Y2SiO5 upconversion material CCK8 in the absence of light.

[0034] Figure 8 0.5mg / ml, 0.75mg / ml, 1mg / mlAg@Pr 3+ : Test chart of survival rate of CCK8 cells with Y2SiO5 upconversion material under light conditions. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.

[0036] Example 1

[0037] (1)(5%Pr 3+ Doping): Pr 3+The preparation method of Y2SiO5 nanoparticles is as follows: prepare 25ml of 0.1mol / L nitric acid Pr(NO3)3 solution. Take 0.663g of yttrium oxide (Y2O3) in a beaker, add 3ml of dilute nitric acid HNO3 to obtain yttrium nitrate solution. Use a pipette to take the above-prepared 3.1ml of nitric acid Pr(NO3)3 solution and add it to 1.5ml of nitric acid with a mass fraction of 65%, then mix it with the yttrium nitrate solution, and seal the beaker with plastic wrap. Heat in a water bath at 80℃ to dissolve, and after dissolution, heat with an electric furnace to remove moisture until the solution becomes viscous, stop heating, and a large amount of crystals appear after cooling. Dry the sample at 104℃. Dissolve the dried sample in an ethanol solution (9.92ml of distilled water and 29.76ml of anhydrous ethanol), and add tetraethyl orthosilicate TEOS to dissolve it.

[0038] 0.62g (TEOS:H2O=1:16), stirred for about 25min. Put it into a 70℃ water bath to form a gel, put the gel into 104℃ drying, and crush the sample with a mortar. Finally, calcine in a muffle furnace, and raise the temperature to 900℃ by program heating at a rate of 8℃ / min. After reaching the set temperature, keep it warm for 3h to obtain Pr 3+ :Y2SiO5 nanoparticles.

[0039] (2) Preparation of yttrium-praseodymium silicate suspension: 0.02 mmol of Pr 3+ : Y2SiO5 nanoparticles were dispersed in 10 mL of water containing 200 μL of acetic acid. Then 20 μL of (3-trimethoxysilylpropyl)diethylenetriamine was added, stirred for 4 h, and the amino-modified nanoparticles were collected by centrifugation, washed twice with deionized water, and finally dispersed in deionized water to obtain a yttrium-praseodymium silicate suspension.

[0040] (3) Preparation of upconversion material: The yttrium-praseodymium silicate suspension prepared in step (2) was heated to 100°C in an oil bath, and then 30ml of an aqueous solution containing 0.3062g (0.0018mol) of silver nitrate (AgNO3) and 0.65ml of KH-550 were added in sequence. After stirring for 20min, 0.3484g (0.0013mol) of trisodium citrate (Trisodium Citrate) containing 20ml of deionized water was added dropwise, and then stirred for another 20min. The precipitate was collected, washed with deionized water 6 times, and vacuum dried at 70°C for 24h. The obtained product was redispersed in 500ml of anhydrous alcohol to obtain silver ion-doped Ag@Pr 3+ : Y2SiO5 upconversion material, for future use.

[0041] (4) Quaternary chitosan was synthesized using chitosan and glycidyl trimethylammonium chloride (GTMAC) as raw materials. 30 g of chitosan was dispersed in 300 ml of water (H2O), and 60.6 g of glycidyl trimethylammonium chloride (GTMAC) was added. The mixture was kept in contact for 24 h under stirring at 60°C. The reaction product was precipitated in acetone, then filtered and dried in an oven at 60°C to obtain quaternary chitosan named N-[(2-hydroxy-3-trimethylammonium)propyl]chitosan chloride (HTCC); 0.24 g of HTCC was dissolved in 5.0 ml of 0.1 M weak acid (lactic acid or acetic acid) solution at 4°C. β-GP (1.0 g) was added to 5.0 ml of deionized water and mixed with the stirred HTCC solution in an ice bath. Finally, 0.5 g of hydroxyethyl cellulose (HEC) was added to obtain GP-HTCC-HEC thermosensitive hydrogel.

[0042] (5) The synthesis of PPY@PDANWs includes the following steps: PPY@PDA: 0.48 mL of pyrrole monomer (PPy) and 0.2 g of dopamine hydrochloride (HCl-PDA) were dissolved in 100 mL of Tris solution (pH = 8.5, 0.01 M) and cooled in an ice-water bath. 2 g of ammonium persulfate ((NH4)2S2O8) was dissolved in 20 mL. The Tris solution was added dropwise to the above solution, stirred vigorously at low temperature, and then transferred to a refrigerator at 8 °C and stirred vigorously for 18 h. After the reaction was completed, the precipitate was washed with deionized water several times and collected by centrifugation. Finally, the washed precipitate was freeze-dried to obtain PP Y@PDA powder.

[0043] (6) Silver ion doping Ag@Pr 3+ :Thermosensitive hydrogel of Y2SiO5 upconversion material: The Ag@Pr 3+ : Y2SiO5 upconversion material powder, GP-HTCC-HEC thermosensitive hydrogel and PPY@PDA were stirred and mixed to prepare the final gel product, which was stored at 0-4°C.

[0044] Example 2

[0045] The difference between Example 2 and step (1) of Example 1 is that the molar doping concentration of praseodymium (0%, 0.5%, 1%, 5%, 8%, 10%, 15%, 20%) is studied. 3+ : The influence of Y2SiO5 fluorescence intensity, other operations are the same as step (1) of Example 1.

[0046] Figure 3The up-conversion emission spectrum of the nanomaterial was tested using a steady-state transient fluorescence spectrometer (FLS1000, Tianmei Instrument Laboratory Equipment (Shanghai), Ltd., UK). The excitation parameters were selected as a filter of 370nm and a slit of 2nm. The figure a on the right represents the emission wavelength of 300nm-400nm under the optimal excitation wavelength of 415nm. When the concentration of praseodymium is 0.5%, the fluorescence intensity is low at this time; when the doping concentration of praseodymium is 1-5%, its fluorescence intensity increases significantly; and when the doping amount of praseodymium element continues to increase to 8-20%, its fluorescence intensity weakens instead, because the high doping concentration will cause fluorescence concentration quenching. Therefore, with the increase of the doping amount of praseodymium element, the fluorescence intensity first increases and then decreases. When the doping amount of praseodymium is 5%, the up-conversion phosphor has a better up-conversion fluorescence effect. At this time, the strongest fluorescence intensity of the sample prepared is about 80000cps. According to the fluorescence spectrum characterization results, praseodymium has a long excited state lifetime, that is, it can stay in the excited state for a relatively long time. When trivalent Pr absorbs 1 415nm light energy, it reaches the excited state energy level, and it can continue to absorb the second 415nm wavelength photon energy, thereby exciting to the 4f-5d orbit, and then the electron returns to the ground state from the 4f-5d orbit, radiating 300-400nm energy photons. In short, when the emission wavelength is 320nm, the excitation band range is 375-700nm, and the emission peak at 415nm is the strongest, so the experiment chooses 415nm as Y2SiO5:Pr 3+ Optimal excitation wavelength for upconversion materials.

[0047] Example 3

[0048] Example 3 is to study different Pr 3+ :Preparation of silver ion-doped Ag@Pr by using Y2SiO5, AgNO3 and trisodium citrate 3+ : The up-conversion fluorescence effect of the Y2SiO5 up-conversion material is the same as that of Example 1 except for the different dosage.

[0049] Table 1:

[0050]

[0051]

[0052] Figure 3 The left side b image detects different Ag@Pr 3+ :Up-conversion emission spectrum of Y2SiO5 combined with fluorescence spectrum Figure 3(b) It is known that the Ag1@Na3 group exhibits the strongest emission light intensity at 310nm under 415nm laser excitation, which is as high as 200000. Therefore, 0.0018mol AgNO3 and 0.0004mol trisodium citrate are selected as the best experimental conditions. Figure 1 Ag@Pr 3 + : Schematic diagram of the preparation of thermosensitive hydrogels of Y2SiO5 upconversion materials. Glycerophosphate (GP) is an organic compound naturally present in the body and is often used as a source of phosphate to treat imbalances in phosphate metabolism. Traditional CS / GP formulations are solutions below or at room temperature and are converted into hydrogels near body temperature. The addition of GP to chitosan solutions promotes the protective hydration of chitosan chains, thereby increasing the aggregation of chitosan chains in neutral pH solutions. Increasing the temperature enhances the hydrophobic interactions between chitosan chains, which is the driving force for the gelation of CS / GP solutions. However, the pH properties have not been reported. HTCC: There are many amino groups on chitosan chains, and hydrogels composed of chitosan have also been used as pH-sensitive drug carriers. Hydrogels prepared from quaternized chitosan have more obvious pH sensitivity. Under acidic conditions, they swell due to the protonation of free amino groups on the chitosan chains and shrink under alkaline conditions. However, previous hydrogels formed by the aggregation and intermolecular interactions of hydrophobic side chains and hydrogen bonds between side chains and the main chain did not show thermosensitivity. Hydroxyethylcellulose (HEC): a cellulose ether prepared by the reaction of alkaline cellulose and ethylene oxide. It is a derivative of cellulose and appears as a white or light yellow powdery solid. The water solubility of hydroxyethyl cellulose is closely related to the degree of substitution of its hydroxyl groups. The greater the degree of substitution, the better its water solubility. Dopamine is mainly related to biological functions and biomedical materials. Its role in the nervous system and the polydopamine materials formed by its self-polymerization have important research and application value. Pyrrole has unique importance in materials science, especially as a precursor of the conductive polymer polypyrrole, which is widely used in electronic devices and bioengineering. Dopamine can self-polymerize under alkaline conditions to form a polydopamine film, which forms a strong bond with the surface. In this process, if pyrrole is present at the same time, dopamine will promote the oxidative polymerization of pyrrole through redox reactions to form a polypyrrole-polydopamine composite material. This composite material not only retains the conductivity of polypyrrole, but also exhibits significantly enhanced adhesion due to the presence of dopamine.

[0053] Figure 2 To characterize the Ag@Pr 3+ :The crystal form of Y2SiO5 samples. Combining PDF@52-1810 and PDF@04-0783 proves that Ag+ Loaded on Ag@Pr 3+ : Y2SiO5.

[0054] Figure 4 Doped with silver ions Ag@Pr 3+ : Characterization diagrams of the temperature-sensitive hydrogel adhesion and temperature sensitivity and modulus of the Ag@Pr:Y2SiO5 upconversion material (observing the state at 0 - 37 °C). The introduction of pyrrole and dopamine endows the composite material with extremely strong adhesion performance. Dopamine self-polymerizes under alkaline conditions to form a polydopamine (PDA) coating, whose structure is similar to that of tendon adhesion protein in marine organisms and can adhere to almost all solid surfaces. Through this mechanism, the composite material can firmly adhere to the surface of biological tissues. Especially when applied to biological implants or wound dressings, it can ensure the stable combination of the material with the in-vivo environment and prevent the material from shifting or falling off. Pyrrole forms conductive polypyrrole (PPy) through polymerization, endowing the hydrogel with conductivity and photothermal response characteristics, which are suitable for electrostimulating tissue engineering or photothermal therapy. In addition, the combination of polypyrrole with metal ions (such as silver ions) further enhances the antibacterial performance of the material, making it perform better in medical applications. The composite hydrogel formed by chitosan and β-glycerophosphate sodium has temperature sensitivity, and its sol-gel phase transition characteristics show significant differences at different temperatures: in a low-temperature environment, the hydrogel presents a solution state and is easy to be minimally invasively delivered by injection; when reaching body temperature (37 °C), the material will in-situ form a gel and stably fill the defect area. This temperature-sensitive property enables drugs or growth factors to be conveniently loaded in the solution state, and the release time and speed of the drug can be controlled by temperature changes to achieve a more precise therapeutic effect. This property is particularly important in the fields of cancer treatment, tissue regeneration, etc., and can reduce the invasiveness of surgery and improve the effectiveness of treatment.

[0055] To explore the effect of temperature on the mechanical properties of the hydrogel, the changes in the storage modulus and loss modulus of the hydrogel are used to visually compare the changes in the mechanical properties of the hydrogel. Among them, G' is the storage modulus and G” is the loss modulus. When G' > G”, it indicates the gel state, and when G' < G”, it is the non-gel state. Shear rate (5 °C / min). G' is less than G”, and the sample is more inclined to the viscoelastic liquid state. Along with the increase in frequency, G' exceeds G”, and the colloid or internal structure of the sample begins to solidify, changing from the liquid state to the solid state.

[0056] Figure 5 For the (GP-HTCC-HEC-Ag@Pr 3+ : Y2SiO5 upconversion material) temperature-sensitive hydrogel SEM characterization diagram. The SEM diagram shows that the composite hydrogel has a loose and porous structure, making the hydrogel have good biocompatibility and be conducive to drug release.

[0057] Figure 6The potential diagram of thermosensitive hydrogel. The introduction of conductive polymers such as polypyrrole (PPy) into hydrogel can give the material the ability to store and transfer charge. Thermosensitive hydrogel undergoes a phase change when the temperature rises, which may lead to an increase in potential, especially in the reaction in the electrolyte solution. As a good conductive material, silver ions can move in the electrolyte solution and participate in the reaction, thereby improving the efficiency of the current, which in turn affects the Ag@Y2SiO5:Pr 3+ The electric potential.

[0058] like Figure 7 As indicated, cytotoxicity was determined by CCK8 assay.

[0059] CCK8 cytotoxicity assay

[0060] 1. Hacat cell plating (96-well plate)

[0061] ① Take the cultured Hacat cells out of the incubator and operate them on a sterile operating table.

[0062] ② Pour out the liquid in the culture medium, wash twice with PBS, 2 ml each time, and pour out.

[0063] ③ Add 2 ml of trypsin and quickly digest in the incubator for 4 minutes. Centrifuge at 1200r / min for 3 minutes and discard the supernatant. The white precipitate at the bottom is the cells.

[0064] ④Add 1 ml of DMEM high glucose medium and resuspend.

[0065] ⑤Cell count. (Unit: 10,000 / ml)

[0066] 2. Add culture medium to complete (6-well plate: 200,000-300,000 per well; 12-well plate: 100,000 / well; 96-well plate: 10,000 / well)

[0068] ①96×10,000=28.8 million cells (300,000 cells per well)

[0069] ② Calculated based on 100-well plates, fearing the cost of the experiment.

[0070] ③10,000×100=1 million cells.

[0071] ④ Volume V = 1 million ÷ unit α million / ml.

[0072] ⑤V÷100=how much V to add to each hole.

[0073] ⑥The total volume of the plate = 96×100ul = 9600ul = 9.6ml.

[0074] ⑦(9.6ml-V)÷100=v of culture medium added to each well.

[0075] 3. Add conversion material (mg / ml)

[0076] (Blank group) control: only culture medium was added without cells

[0077] (Control group) 0: Add culture medium, add cells (Experimental group) 1.5625-1600 mg / ml: Different concentrations of Ag@Pr 3+ : Y2SiO5 material + culture medium + add cells.

[0078] 4. Drug administration

[0079] ① Prepare the diluted drug and weigh 1.28 mg of Ag@Pr 3+ :Y2SiO5, add 1600ul culture medium into EP tube, and prepare 800ug / mg Ag@Pr according to the maximum concentration 3+ :Y2SiO5. Add 800ul culture medium to each of the remaining tubes.

[0080] ② Dilute gradually, add 1600ul to the tube with the highest concentration, mix well and pipette 800ul into the second tube.

[0081] ③Only the last tube is 1600ul.

[0082] ④Finally, the top and bottom are PBS without cells, and only 6 wells with PBS are aspirated as the blank group.

[0083] 5. Determination

[0084] Principle: CCK-8 reagent contains WST-8: Chemical name: 2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfonic acid benzene)-2H-tetrazole monosodium salt, which is reduced to a highly water-soluble yellow formazan product by dehydrogenase in the cell mitochondria under the action of the electron carrier 1-methoxy-5-methylphenazine dimethyl sulfate. The amount of formazan generated is proportional to the number of living cells. The absorbance value (OD value) is measured at a wavelength of 450nm using an enzyme marker to determine the number of living cells. The larger the OD value, the stronger the cell activity (if it is to measure drug toxicity, it means that the drug toxicity is less).

[0085] ① Add 10uL of CCK-8 solution to each well and continue incubation at 37℃ for 3h.

[0086] ②Terminate the culture and measure the absorbance of each well at 600 nm using an enzyme-labeled instrument.

[0087] ③ Calculate the maximum non-toxic concentration of the drug to the cells. Viability calculation: Cell viability*(%) = [A(drug added)-A(blank)1 / [A(0 drug added)-A(blank)]×100.

[0088] Results The prepared upconversion material had low toxicity and could significantly inhibit the proliferation of keratinocytes under light conditions. Figure 7 The results show that the prepared upconversion materials have low toxicity. Figure 8 In contrast, the proliferation of keratinocytes can be significantly inhibited under light conditions. 3+ :Y2SiO5 upconversion material has low cytotoxicity. 0.5mg / ml-1mg / ml can be administered at a concentration. Combined with the comparison of cell survival rates under 415nm visible light illumination and dark conditions, it is concluded that 1mg / ml is the best administration concentration, which can kill cells to about 60%.

[0089] Figure 8 It can be seen that because the cell survival rate in the 0-1 (mg / L) range decreases step by step, three concentrations of 0.5, 0.75, and 1 mg / L were selected for dark and light experiments to explore the optimal drug concentration. It was concluded that when the drug concentration was 1 mg / L, Hacat and DC could most effectively achieve upconversion luminescence under light conditions to kill cells.

[0090] And at a concentration below 1 mg / ml, Ag@Pr 3+ : Y2SiO5 upconversion materials have low cytotoxicity.

[0091] The dosing concentration of 0.5mg / ml-1mg / ml was tested. Combined with the comparison of cell survival rates under 415nm visible light illumination and dark conditions, it was concluded that 1mg / ml was the best dosing concentration, which could kill about 60% of the cells.

[0092] like Figure 8 As shown, the median lethal dose of the upconversion patch is LogLD50 = (Xk-i∑p-0.5). Xk is the highest logarithmic dose, i is the difference between two adjacent logarithmic doses; P is the mortality rate of each dose group. The median lethal dose of the upconversion patch is 1.168 mg / ml.

[0093] The embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For professionals in the relevant field, other different forms of changes or modifications can be made based on the above embodiments, and it is not necessary and impossible to list all implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A silver ion-doped Ag@Pr 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: Doping silver ions with Ag@Pr 3+ :Y2SiO5 upconversion material and thermosensitive hydrogel material are mixed to prepare silver ion-doped Ag@Pr 3+ : Thermosensitive hydrogel of Y2SiO5 upconversion material; Among them, silver ion doped Ag@Pr 3+ :The preparation method of Y2SiO5 upconversion material is: (1) First prepare Pr 3+ :Y2SiO5 nanoparticles, which were modified with amino groups, and the amino-modified Pr 3+ :Y2SiO5 nanoparticles were dispersed in deionized water to obtain Pr 3+ : Y2SiO5 suspension; (2) Pr 3+ : The Y2SiO5 suspension was heated to 90-110°C, and then silver nitrate and KH-550 aqueous solutions were added. After stirring, trisodium citrate solution was added dropwise. After stirring, the precipitate was collected, washed and dried to obtain Ag@Pr 3+ :Y2SiO5 upconversion material.

2. The silver ion-doped Ag@Pr according to claim 1 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: Step (1) Pr 3+ : In Y2SiO5 nanoparticles, the theoretical molar amount of Pr in Y2SiO5 is 1-15%; 3+ : Y2SiO5 nanoparticles are obtained by calcining at 900℃.

3. The silver ion-doped Ag@Pr according to claim 1 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: Amination modification: Pr 3+ :Y2SiO5 nanoparticles were dispersed in water containing acetic acid, then KH-550 was added, stirred and centrifuged to collect amino-modified Pr 3+ : Y2SiO5 nanoparticles.

4. The silver ion-doped Ag@Pr according to claim 1 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: In step (2), Pr 3+ : The molar ratio between Y2SiO5, silver nitrate and trisodium citrate is 0.02:0.0009~0.0036:0.0001~0.0026.

5. The silver ion-doped Ag@Pr according to claim 1 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: The preparation method of the thermosensitive hydrogel is as follows: (1) chitosan and glycidyl trimethylammonium chloride are used to synthesize quaternary chitosan, the quaternary chitosan is dissolved in a weak acid, and then β-glycerophosphate and hydroxyethyl cellulose are added to obtain GP-HTCC-HEC thermosensitive hydrogel after reaction; (2) polymerizing pyrrole and dopamine hydrochloride to generate PPY@PDA; (3) Ag@Pr 3+ :Y2SiO5 upconversion material dispersion, GP-HTCC-HEC thermosensitive hydrogel, PPY@PDA were mixed and stirred to prepare silver ion-doped Ag@Pr 3+ : Thermosensitive hydrogel of Y2SiO5 upconversion material.

6. The silver ion-doped Ag@Pr according to claim 5 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: In step (1), the mass ratio of quaternized chitosan, β-glycerophosphate and hydroxyethyl cellulose is 0.1-0.5:2:

1.

7. The silver ion-doped Ag@Pr according to claim 1 3+ : A method for preparing a thermosensitive hydrogel of a Y2SiO5 upconversion material, characterized in that: The molar ratio of pyrrole to dopamine hydrochloride is 6 to 8:

1.

8. Silver ion-doped Ag@Pr prepared by the method according to any one of claims 1 to 7 3+ : Thermosensitive hydrogel of Y2SiO5 upconversion material.

9. Silver ion-doped Ag@Pr prepared by the method according to any one of claims 1 to 7 3+ :Application of thermosensitive hydrogel based on Y2SiO5 upconversion material in wound dressing.